1997
DOI: 10.1161/01.atv.17.6.1157
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Folic Acid Supplementation on Plasma Total Homocysteine Are Modulated by Multivitamin Use and Methylenetetrahydrofolate Reductase Genotypes

Abstract: Elevated concentration of plasma total homocysteine (tHcy) is a common risk factor for arterial occlusive diseases. Folic acid (FA) supplementation usually lowers tHcy levels, but initial tHcy and vitamin levels, multivitamin use, and polymorphisms in the gene for 5, 10-methylenetetrahydrofolate reductase (MTHFR) may contribute to variability in reduction. We tested the effects of a 3-week daily intake of 1 or 2 mg of FA supplements on tHcy levels in patients with and without coronary heart disease (CHD) who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
3
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(122 citation statements)
references
References 17 publications
11
106
3
2
Order By: Relevance
“…This seems to agree with the idea that high tHcy levels are present in the plasma of homozygous subjects with the MTHFR mutation only under a certain folate concentration, whereas low folate levels per se affect the homocysteine pathway. 4,28,41 We found a significantly higher number of subjects with vitamin deficiencies in cases than in controls, implying a significant association between VTE and low vitamin levels. When the two groups were completely adjusted for age, sex, and menopausal condition, 34,42 the new ORs remained significant only for low folate levels, suggesting that some form of decreased vitamindependent enzyme activity may be connected to thrombosis.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This seems to agree with the idea that high tHcy levels are present in the plasma of homozygous subjects with the MTHFR mutation only under a certain folate concentration, whereas low folate levels per se affect the homocysteine pathway. 4,28,41 We found a significantly higher number of subjects with vitamin deficiencies in cases than in controls, implying a significant association between VTE and low vitamin levels. When the two groups were completely adjusted for age, sex, and menopausal condition, 34,42 the new ORs remained significant only for low folate levels, suggesting that some form of decreased vitamindependent enzyme activity may be connected to thrombosis.…”
Section: Discussionmentioning
confidence: 61%
“…[3][4][5] Thermolabile MTHFR is the most frequent inherited defect of the homocysteine pathway. Individuals homozygous for the MTHFR mutation have significantly higher tHcy levels than heterozygotes or normal homozygotes, 27,28,40 and they can have an increased risk for arterial thrombosis. [17][18][19] Because not all studies have reported a direct association between C677T homozygosity and VTE, 15,16,20 -22 it is possible that hyperhomocystinemia plays a greater role in developing VTE than C677T homozygosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, the level of plasma homocysteine can be lowered in homozygous individuals by folic acid supplementation. 17 About half the general population carries at least one mutated allele and the frequency of the homozygous mutated genotype (677TT) ranges from 1 to 20% depending on the population. 18 A second common polymorphism in the MTHFR gene is a 1298A?C transition (A1298C) which results in a glutamate to alanine substitution within a presumed regulatory domain of MTHFR.…”
Section: Introductionmentioning
confidence: 99%
“…(33) Hcy is an intermediate product of the amino acid methionine and is metabolized by 2 pathways: re-methylation, which recreates methionine, and trans-sulfuration, which converts homocysteine into taurine. (34)(35)(36)(37) The re-methylation pathway transfers a methyl group to Hcy through methylcobalamin, an activated form of B-12 (which receives its methyl group from Sadenosylmethionine (SAMe) or though 5-methyltetrahydrafolate (5-MTHF), an active form of folic acid) or betaine (Trimethylglycine). (37) The structure most commonly identified as vitamin B12 is cyanocobalamin; however, this molecule does not occur naturally, to any extent, in plants, microorganisms or in animals.…”
Section: Homocysteinementioning
confidence: 99%